(untitled) (Research, Society and Development, 2021)
Bar soaps with antiseptic action are intended for cleaning residues present in the body, their use has grown significantly due to the population’s concern about certain diseases caused by microbiological contamination. With this, different brands of soaps have appeared on the market, guaranteeing the elimination of 99.9% of bacteria. The aim of this study was to perform a comparative analysis of pH, antibacterial activity and labels of 5 different brands of antibacterial bar soaps, identified as A, B, C, D and E. The pH was determined with the aid of a digital pH meter, and in the microbiological analysis, the disk diffusion methodology was used in order to observe the presence or absence of the multiplication of the bacteria Streptococcus pyogenes, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus epidermidis, Staphylococcus aureus and Escherichia coli against the different soaps tested. During the analysis of the labeling of the soaps, the presence of the “composition” requirement required by the current resolution was evaluated. In the tests carried out it was found that the pH of all tested brands were outside the established parameters. In the microbiological analysis, it was observed that only the E mark showed an antiseptic effect against the tested bacteria. The other soaps showed less and even no potential to inhibit the growth of these microorganisms. The products analyzed in this study present in their formulations two active substances, triclosan and triclocarban, however they can be harmful to human health and the environment, and induce bacterial resistance, therefore, some countries have already banned the use of these assets. According to the results obtained, it is possible to conclude that the labels present on the packaging of these different brands analyzed are at variance with that established by the manufacturers.